Pengaruh model realistic mathematics education (RME) terhadap kemampuan pemecahan masalah dalam menggunakan soal cerita pada kelas VII SMP Negeri 1 Sei Kepayang - Syaputra, Dedi Ahmad; Nurani, Dini; Umami, Reza (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
The purpose of this study was to determine whether there is an effect of the Realistic Mathematics Education (RME) Model on Problem Solving Ability in using story problems in class VII SMP. This type of research is a quasi-experimental research design with two groups pretest and posttest. The population in this study were all classes off grade VII. The research sample consisted of 2 classes (class VII-A and VII-B) which were taken by cluster random sampling. In class VII-A as the experimental class using the Realistic Mathematics Education (RME) Model and in class VII-B as the control class using Direct Intruction Model. After the learning is complete, a posttest is obtained with the average results of the class and control class The results of the t test are obtained then Ha is accepted, thus it is obtained that there is an effect of the Realistic Mathematics Education (RME) Model on Problem Solving Ability in using story questions on comparison material Class VII SMP.